Pengaruh Investasi dan IPM terhadap Pertumbuhan Ekonomi Hijau di Provinsi Kalimantan Timur - Aldy Friyatna Dira; Kurniawan Prambudi Utomo; Mic Finanto Ario Bangun; Eigis Yani Pramularso; Faroman Syarief (UNIVED Press, 2023)
Sustainable and environmentally friendly economic growth has become a major focus for many regions today. This study aims to analyze the effect of investment and the Human Development Index (IPM) on green economic growth in West Kalimantan. The research method used in this study is multiple regression analysis with descriptive statistics using secondary data collected from various sources such as government reports, academic publications, and others. The dependent variable in this study is green economic growth, while the independent variables are investment and HDI. The results show that investment in the green economy sector has a significant positive impact on green economic growth. These investments include investments in the green infrastructure economy, this finding shows that strategically directed investments in these sectors can promote sustainable economic growth and reduce negative impacts on the environment and increase the HDI with indicators such as health, and decent living, levels of education, and per capita expenditure, which are important factors in achieving sustainable development.